New discoveries at Mokarta, a Bronze Age hilltop settlement in western Sicily. (June 2020) - Sevara, Christopher; Salisbury, Roderick B.; Totschnig, Ralf; Doneus, Michael; Löcker, Klaus; Tusa, Sebastiano
Abstract: Abstract : Extensive settlement activity at the Bronze Age site of Mokarta in western Sicily has previously been inferred, but the extent and condition of its subsurface remains have never been established. The authors use geophysical prospection, historical and modern remote-sensing data and soil chemistry to identify previously undocumented structures and activity areas extending beyond those exposed by previous excavations. This exercise not only has implications for the multifaceted social organisation of Late Bronze Age communities in Sicily, but, more generally, demonstrates how minimally invasive investigative techniques combined with existing data can reveal subsurface archaeological sites and the impact of post-depositional processes.